Evaluation of pain in the paediatric patient admitted to sub-intensive care: a scoping review protocol - Granata, Carlotta; Guasconi, Massimo; Ambrosi, Federica; Anderle, Lucrezia; Marone, Beatrice; Dimonte, Doriana; Tumbiolo, Federica; Bassi, Maria Chiara; Anderson, Gloria; Sarli, Leopoldo; Artioli, Giovanna; Bonacaro, Antonio (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: pain is considered as the 5th vital sign thus it’s paramount that healthcare professionals are equipped with validated tools for his correct assessment. There are different paediatric pain assessment scales that take into account patients’ age. Actually, the “Face, Legs, Activity, Cry, Consolability” (FLACC), Wong-Baker and NRS scales are regarded as the gold standard in low intensity clinical areas, while the COMFORT-Behavior (COMFORT-B) and Behavioral Pain Scale (BPS) ones are used for high intensity clinical areas where paediatric patients are sedated/intubated. It’s unclear which pain assessment scale should be used in sub-intensive areas such as Sub-Paediatric Intensive Care Unit (Sub-PICU) e Sub-Neonatal Intensive Care Unit (Sub-NICU). The aim of this protocol is to map the literature in order to identify what evidences are available regarding the assessment of pain in the paediatric sub-intensive clinical areas. Research question: “What is the literature available on pain assessment in paediatric patients in sub-intensive clinical areas such as Sub-PICU and sub-NICU?”. Source of evidence: literature search will be performed through the following databases: PubMed, Scopus, CINAHL, Cochrane Library, Open Dissertations (EBSCO) and DOAJ. Furthermore, Cochrane CENTRAL and ClinicalTrials.gov will also be included. Methods: this scoping review will be conducted in accordance to the Joanna Briggs Institute guidelines and the results presented through a PRISMA flowchart. Review registration: Open Science Framework https://doi.org/10.17605/OSF.IO/8KBRQ